The Application of Tapak Dara (Catharanthus roseus) Extract Ointment Reducing IL-6 and MMP-1 Production in Photodamaged Rat's Skin - Desiani Putri Ramayanti; Agung Putra; Titiek Sumarawati (Universitas Sebelas Maret, 2026)
Tapak dara Catharanthus roseus (L.) Don extract possesses promising properties that could counteract the detrimental effects of UV-B exposure. Its inherent antioxidant and anti-inflammatory capabilities suggest its potential as a therapeutic agent for managing UV-B-induced skin damage. This study aims to analyze the effect of tapak dara extract ointment on IL-6 and MMP-1 levels in photodamaged skin. Twenty-five healthy male Wistar rats were divided into two groups: a healthy control group (n = 5) and a UVB-exposed group (n = 20). The UVB-exposed rats received 1 MED for 8 minutes per day, for 10 sessions over 14 days. Skin tissue was collected on day 15 to assess skin damage and validate collagen loss using immunohistochemistry. After validation, photodamaged skin rats were divided equally into four experimental groups: placebo (P2), vitamin E (P3), tapak dara extract 10% (P4), and 20% (P5). The rats were sacrificed at the end of the study, and the skin tissues were analyzed for IL-6 and MMP-1 using ELISA. Based on the analysis results, groups P4 and P5 produced average levels of IL-6 and MMP-1 that were significantly lower than those in P2 (p < 0.050). IL-6 and MMP-1 levels in group P5 reached 188.60 ± 40.60 pg/mL and 1,611 ± 344 pg/mL, respectively. This is likely due to the secondary metabolite content of tapak dara, which acts as an antioxidant and anti-inflammatory, suggesting it has potential as a photodamaged skin therapy. As many as 20% tapak dara extract cream effectively reduces IL-6 and MMP-1 levels in UV-B-exposed skin tissue. However, this study did not evaluate changes in skin tissue after treatment with tapak dara extract. Therefore, further research is needed to analyze and validate collagen synthesis following treatment with tapak dara extract.